EGFR mutation based on lung laterality in adenocarcinoma type of non-small cell lung cancer - Ryan Feraldy Haroen; Paranita Ferronika; Rita Cempaka; Indrawati; Bening Rahimi Titisari; Vincent Lau; Andrew Nobiantoro Gunawan; Brigitta Natasya Halim; Vincent Laiman; Lina Choridah; Didik Setyo Heriyanto (Published by Universitas Gadjah Mada, 2024)
Targeted therapies have shown promise in improving survival rates for lung adenocarcinoma, a common and deadly malignancy. EGFR-targeting tyrosine kinase inhibitors (TKIs) are particularly effective among these therapies in cases with EGFR mutations. Detecting these mutations before TKI treatment is essential. Various radiological features have been linked to EGFR mutations. However, the relationship between tumor location and mutation types in Indonesian lung adenocarcinoma patients remains unexplored. This study aimed to identify the frequency of EGFR mutation in local lung adenocarcinoma cases based on the tumor location. Clinical data of lung adenocarcinoma patients (n = 272) diagnosed between 2018 and 2022 were retrospectively taken from the Department of Anatomical Pathology, Dr. Sardjito General Hospital, Yogyakarta. The qRT-PCR data of EGFR mutation status was obtained from the Department of Anatomical Pathology, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta. Descriptive analysis was performed using STATA version 14.0. EGFR mutations were found in 60.7% of patients, with 58.2% having exon 19 mutations and 21.2% exhibiting exon 21 L858R mutations. Mutation status was found to be significantly different based on the patient's gender (p = 0.022) and age (p = 0.029) but not with lung laterality (p = 0.093). The proportion of exon 19, exon 21 L858R, and uncommon mutations in the right and left lung adenocarcinoma was similar across all samples. This study found no difference between specific EGFR mutation types and tumor location in lung adenocarcinoma.